Ameliorative Effect of Berberine on Neonatally Induced Type 2 Diabetic Neuropathy via Modulation of BDNF, IGF-1, PPAR-γ, and AMPK Expressions - Guangju Zhou; Mingzhu Yan; Gang Guo; Nanwei Tong (SAGE Publishing, 2019)
Neonatal-streptozotocin (n-STZ)-induced diabetes mimics most of the clinicopathological symptoms of type 2 diabetes mellitus (T2DM) peripheral neuropathy. Berberine, a plant alkaloid, is reported to have antidiabetic, antioxidant, anti-inflammatory, and neuroprotective potential. The aim of the present study was to investigate the potential of berberine against n-STZ-induced painful diabetic peripheral polyneuropathy by assessing various biochemical, electrophysiological, morphological, and ultrastructural studies. Type 2 diabetes mellitus was produced neonatal at the age of 2 days (10-12 g) by STZ (90 mg/kg intraperitoneal). After confirmation of neuropathy at 6 weeks, rats were treated with berberine (10, 20, and 40 mg/kg). Administration of n-STZ resulted in T2DM-induced neuropathic pain reflected by a significant alterations ( P < .05) in hyperalgesia, allodynia, and motor as well as sensory nerve conduction velocities whereas berberine (20 and 40 mg/kg) treatment significantly attenuated ( P < .05) these alterations. Berberine treatment significantly inhibited ( P < .05) STZ-induced alterations in aldose reductase, glycated hemoglobin, serum insulin, hepatic cholesterol, and triglyceride levels. The elevated oxido-nitrosative stress and decreased Na-K-ATPase and pulse Ox levels were significantly attenuated ( P < .05) by berberine. It also significantly downregulated ( P < .05) neural tumor necrosis factor-α (TNF-α), interleukin (IL)-1β and IL-6 messenger RNA (mRNA), and protein expressions both. Streptozotocin-induced downregulated mRNA expressions of brain-derived neurotrophic factor (BDNF), insulin-like growth factor (IGF-1), and peroxisome proliferator-activated receptors-γ (PPAR-γ) in sciatic nerve were significantly upregulated ( P < .05) by berberine. Western blot analysis revealed that STZ-induced alterations in adenosine monophosphate protein kinase (AMPK; Thr-172) and protein phosphatase 2C-α protein expressions in dorsal root ganglia were inhibited by berberine. It also attenuated histological and ultrastructural alterations induced in sciatic nerve by STZ. In conclusion, berberine exerts its neuroprotective effect against n-STZ-induced diabetic peripheral neuropathy via modulation of pro-inflammatory cytokines (TNF α, IL-1β, and IL-6), oxido-nitrosative stress, BDNF, IGF-1, PPAR-γ, and AMPK expression to ameliorate impaired allodynia, hyperalgesia, and nerve conduction velocity during T2DM.